Immediate Effects of Functional Electrical Stimulation-Assisted Cycling on the Paretic Muscles of Patients With Hemiparesis After Stroke: Evidence From Electrical Impedance Myography - Li, Le; Hu, Chengpeng; Leung, Kenry W. C.; Tong, Raymond K. Y. (Frontiers in Aging Neuroscience, 2022)
Background Electrical impedance myography (EIM) has been applied to assess muscle health conditions in neuromuscular disorders. This study aimed to detect immediate muscle electrical impedance properties alterations in lower extremity of chronic stroke survivors right after functional electrical stimulation (FES) assisted cycling training. Methods Fourteen chronic stroke survivors were recruited in current study. EIM measurements were conducted before and immediately after 40-minute FES assisted cycling training for each subject. Four interested muscle groups (rectus femoris (RF), biceps femoris (BF), tibialis anterior (TA), the medial head of gastrocnemius (MG)) were selected. Correlation analysis was performed to reveal correlation between changes of EIM parameters and clinical scales (Fugl-Meyer Assessment of lower extremity (FMA-LE); six-minute walking test (6MWT). Results Right after training, reactance (X) and phase angle (θ) values significantly increased on the TA and MG muscles. Significant correlation was observed between X value and FMA-LE scores (r = 0.649 p = 0.012) at MG as well as X, and FMA score of the ankle joint (r = 0.612 p = 0.02). Resistance (R) and θ value were significantly correlated to 6MWT score (X-6MWT: r = 0.651 p = 0.012, θ-6MWT: r = 0.621 p = 0.018). Conclusions This brief report demonstrated that EIM can reveal the intrinsic properties alteration in paretic muscle right after FES cycling. These alterations might be related to muscle hypertrophy (ie. increases of muscle fiber size). This brief report might aid the understanding of the mechanism of electrical stimulation assisted exercise in improving muscle function of stroke survivors.